Neuropathic pain: presentation, mechanisms and management - Wells, Chris (Henry Stewart Talks, 2009)
Neuropathic pain: definition and classification, Shingles and Post Herpetic Neuralgia (PHN), Pain character, Histological changes, CRPS, Brain damage, Central post-stroke pain, SCI: traumatic and degenerative, Trigeminal neuralgia: diagnostic criteria, Epidemiology, Symptoms of neuropathic pain, Allodynia, Diagnosing neuropathic pain, Quantitative sensory testing, Altered sensation, Localized symptoms, Dysaesthesia, Hyperalgesia, Paraesthesia, Hyperaesthesia, Mechanisms, Co-morbidity associated with peripheral neuropathic pain, Algorithm for neuropathic pain treatment, TCADs and other anti-depressants, Anticonvulsants, Cannabinoids, Topicals, Blocks/interventions, Neural blockade, Infusions and implants, Neurosurgical, Percutaneous interventions, Positive drug trials in SCI